Reconnaissance for a Uranothorianite-Bearing Lode in the Vicinity of the Headwaters of the Peace River, Candle Quadrangle, Seward Peninsula, Alaska - West, Walter S. (United States. Government Printing Office., 1952)
From abstract: Reconnaissance in 1947 found uranothorianite and gummite associated with copper sulfides, iron oxides, molybdenite, gold, silver, bismuth, and thorite in placers of a headwater tributary of the Peace River in the eastern part of the Seward Peninsula, Alaska. Brief radiometric reconnaissance early in the summer of 1952 failed to locate the bedrock source of the radioactive minerals at the head of the Peace River, primarily because of the shielding-effect of widespread tundra cover. The samples obtained in 1952 indicate the presence of galena, sphalerite, pyrrhotite, covellite, and fluorite in addition to the minerals reported in the results of the 1947 reconnaissance.